EFFECT OF AMPICILLIN AND CHLORAMPHENICOL ON CHICK SERUM - Nanda, Harshit; V, Suneetha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
<!--[if gte mso 9]> <![endif]--> Objective: Cystatin protein present in chick serum exhibits antimicrobial activity. The present study focuses on the effect of ampicillin and chloramphenicol antibiotics on chick serum and thus verifies Beer–Lambert's law. Methods: The serum is separated from the cellular matter with the help of a micropipette to get a clean serum sample. The quantification of protein was done by Lowry's method. The antibiotics ampicillin and chloramphenicol stock solution were prepared by 10 mg of antibiotic powder in 10 ml of sterilized water. The statistical analysis of the values obtained was done by SPSS logistics software. Results: The different values of concentration of serum with absorption showed a linear relationship which verifies Beer–Lambert's law. With an increase in the concentration of protein in chick serum, the absorption also increases, which gives a range of concentration of protein at which ampicillin and chloramphenicol act. Conclusion: The rise and fall in the absorbance rate of proteins after addition of different antibiotics represent the increase and decrease in the concentration of proteins, respectively. This shows that every antibiotic acts at a particular concentration on the protein of the serum. Therefore, proper doses of antibiotics are recommended by the doctors. <!--[if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->